Pelatihan Keterampilan Konseling Multikultural Bagi Guru Bimbingan Dan Konseling Tingkat Sekolah Menengah Atas Kota Barabai - Sanjaya; Aminah (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
To deal with students from different cultural backgrounds (multicultural) it is very appropriate to be handled by the Guidance and Guidance Teacher. SMA in Barabai City is a school that has students and teaching staff who have ethnic, cultural and religious diversity. However, the teaching staff in the city of Barabai in terms of knowledge and skills for understanding multicultural counseling is still lacking. The aim of carrying out this community service activity is so that teaching staff, especially high school level guidance and counseling teachers in Barabai City, have the knowledge and skills to handle students who have socio-cultural problems. The method used is lecture and question and answer techniques with a duration of 2x60 minutes with the topic of delivering material on basic concepts and the urgency of multicultural counseling in schools. The targets of the activities taken were 25 guidance and counseling teachers who were members of the Barabai City High School MGBK. The results obtained are improvements in community values ​​(arts, culture, social, politics, security, peace, education and health) at Barabai City High School.